2017
DOI: 10.2134/agronj2017.05.0282
|View full text |Cite
|
Sign up to set email alerts
|

Late‐Split Nitrogen Applications Increased Maize Plant Nitrogen Recovery but not Yield under Moderate to High Nitrogen Rates

Abstract: N itrogen fertilizer is a high-cost input for maize production that is diffi cult to manage because efficient crop accumulation and utilization is dependent on agronomic, genetic, biological, and environmental factors. Within the wide spectrum of N fertilizer management decisions, a key interest has been improving the effi ciency with which N fertilizers are used by optimizing N rate and the timing of N application. One way to pursue increased N fertilizer effi ciency may be with the use of late-season, split … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
52
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 44 publications
4
52
3
Order By: Relevance
“…To ensure that the older hybrids were not negatively affected by the use of a common plant density, an additional plant density experiment was also conducted in 2015 and 2016. That experiment, described further in Mueller et al (2017), found no hybrid × plant density interaction for grain yield and, therefore, it was concluded that the use of a single plant density would not materially alter the relative hybrid treatment results of this experiment. All hybrids were treated with in‐furrow insecticide at planting to mitigate differences in genetic insect resistance.…”
Section: Methodsmentioning
confidence: 63%
“…To ensure that the older hybrids were not negatively affected by the use of a common plant density, an additional plant density experiment was also conducted in 2015 and 2016. That experiment, described further in Mueller et al (2017), found no hybrid × plant density interaction for grain yield and, therefore, it was concluded that the use of a single plant density would not materially alter the relative hybrid treatment results of this experiment. All hybrids were treated with in‐furrow insecticide at planting to mitigate differences in genetic insect resistance.…”
Section: Methodsmentioning
confidence: 63%
“…Timing of nitrogen fertilizer applications plays a role in uptake. Depending on weather conditions, nitrogen uptake after silking can range from 22.4 to 40.8% of the total nitrogen uptake by the plant (Mueller et al, 2017).…”
Section: Nitrogen Recommendation Challengesmentioning
confidence: 99%
“…Monitoring a measurement like NRE as a part of this system over time can help producers and consultants identify the external impact on nitrogen fertilizer applications. For example, Mueller et al (2017) found a yield response and an NRE improvement in the growing season where rainfall was limited in 32 days between the first and the second nitrogen applications compared with when rainfall was higher in other seasons.…”
Section: Adaptive Managementmentioning
confidence: 99%
See 2 more Smart Citations